The measurement model of geo-education among trainee teachers in Malaysia - Mat Rahimi Yusof; Mohd Faiz Mohd Yaakob; Aliff Nawi; Hapini Awang; Dayang Rafidah Syariff M. Fuad; Aizuddin Md Rami (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study conducted to develop a measurement model for measuring Geo-Education in Malaysia context. This cross-sectional survey involved 245 trainee teachers in Universities and Institut Pendidikan Guru Malaysia (IPGM). The data collection was made through a set of questionnaires and analyzed using SEM-AMOS. There are four main elements measured, which are loading factors, convergent validity, discriminant validity, and composite reliability. The findings indicated that Geo-Education had a significant contribution to the proposed constructs, namely primer, issues, ecosystem, lifestyle, and cross-curricular elements. A model of Geo-Education was successfully developed in this study using these five constructs, namely primer, issues, ecosystem, lifestyle, and cross-curricular elements. This study also identified twenty-five behaviours of Geo-Education among the trainee teachers in Malaysia. The findings of this study are essential as a guideline for Malaysian teachers to implement the concept of Geo-Education in Malaysia. Additionally, the application of this subject as cross-curricular elements in the Malaysian curriculum is essential to ensure the success of the implementation of Education Sustainable Development (ESD) in the school environment.